Optimization of Direction and Control Functions in Improving SOAP Writing in CPPT at X Hospital - Tanlain, Susana Helen; Afriani, Tuti; Mashudi, Dudi (Budapest International Research and Critics University, 2021)
The provision of patient care in hospitals is carried out based on the concept of Patient-Centered Care (PCC). One of the dimensions of this PCC is the coordination and integration of care services. The integration of care services is carried out horizontally and vertically. The care provider professionals work as intra and interdisciplinary with interprofessional collaboration, assisted by an integrated patient development record written in SOAP form. As the most caregivers in hospitals, nurses must correctly record and document every patient's progress so that other professions can quickly use them. The phenomenon that occurs, doctors do not read or do not believe in the writings of nurses. Hospital X is a type a hospital, specifically in the intensive care unit; the average BOR in the last three months is 69.71%. Based on the observations, it was found that the writing of SOAP on integrated patient development records was not the same for every NurseNurse and not following the standards. So it is necessary to optimize the direction and control function of the Charge Nurse and the head of the room for writing SOAP on integrated patient development records to comply with Nursing Care Standards and SOPs for Hospital X. The method used is a pilot project, starting from data identification, problem analysis, problem priority setting, Plan Preparation of Action (POA), implementation, and evaluation. Data were collected by interview, observation, and survey methods using a google form containing questions about the knowledge and perceptions of nurses on writing SOAP on the integrated patient development record. With the direction and control/control, each level of the manager is expected to achieve organizational goals and improve the deviations found. For this reason, it is hoped that the hospital can accelerate the implementation of EMR synchronized with the nursing care standards that have been arranged and continue to carry out regular supervision in writing SOAP on the integrated patient development record.